OP0075 PAR2 ACCELERATES OSTEOARTHRITIS-LIKE JOINT CHANGES IN A MURINE MODEL OF POST-TRAUMATIC OSTEOARTHRITIS. (June 2019) - Mcculloch, Kendal; Huesa, Carmen; Dunning, Lynette; Hof, Rob Van't; Lockhart, John; Goodyear, Carl
Abstract : Background: Post-traumatic osteoarthritis (PTOA) is associated with articular cartilage damage and represents a major clinical challenge due to the poor regenerative capability of cartilage. We have recently developed a novel and robust dual injury murine model of PTOA, which combines destabilisation of the medial meniscus (DMM) and cartilage scratch 1 . This model results in accelerated OA-like symptoms including enhanced osteophyogenesis. Prior studies in the DMM model have demonstrated that absence of proteinase-activated receptor 2 (PAR2) in mice results in significant protection from early OA-like symptoms 2, 3 . Objectives: To investigate if the absence of PAR2 confers protection in a dual injury PTOA murine model. Methods: PTOA was induced in both male C57BL/6 wild-type (WT) and PAR2 -/- mice, via combined destabilisation of the medial meniscus and cartilage scratch (DCS). Twenty-eight days post-surgery, osteophytogenesis and bone changes were monitored using microcomputed tomography. Dynamic weight bearing was assessed as an indirect measurement of pain at day 14. Results: Evaluation of the presence and number of osteophyte revealed no significant differences between WT and PAR2 -/- mice at day 28. However, quantification of osteophytes revealed that PAR2 -/- mice had significantly smaller osteophytes (p=0.006) with less mineralised bone (p=0.003). Moreover, analysis of metaphyseal trabecular bone on the operated leg showed a significant decrease in% bone volume/tissue volume (BV/TV) (p=0.025). Assessment of pain-related behaviour, using dynamic weight bearing at day 14, demonstrated that PAR2 -/- mice exerted less load on their front paws. Conclusion: The findings in this study show that PAR2 plays a role in accelerated OA-like symptoms (i.e., osteophyte formation) in a dual injury model of OA, where both destabilisation of the medial meniscus and cartilage damage drive disease pathology. Furthermore, the loss of PAR2 decreases pain behaviour suggesting that PAR2 is involved in pain sensing. Taken together, these results support the future exploration of PAR2 as a therapeutic target for PTOA. References: [1] McCulloch K, Huesa C, Dunning L, van 't Hof R, Lockhart J, Goodyear CS. Accelerated Osteoarthritic-like Symptoms in a Novel Dual Injury Model Combining Destabilisation of the Medial Meniscus and Cartilage Damage. Journal of Bone and Mineral Research. 2018; 33:155 [2] Huesa C, Ortiz AC, Dunning L, McGavin L, Bennett L, McIntosh K, Crilly A, Kurowska-Stolarska M, Plevin R, van 't Hof RJ, et al. Proteinase-activated receptor 2 modulates OA-related pain, cartilage and bone pathology. Ann Rheum Dis. 2016;75:1989-97. [3] Ferrell WR, Kelso EB, Lockhart JC, Plevin R, and McInnes IB. Protease-activated receptor 2: a novel pathogenic pathway in a murine model of osteoarthritis. Annals of the Rheumatic Diseases. 2010;69:2051. Disclosure of Interests: Kendal McCulloch: None declared, Carmen Huesa: None declared, Lynette Dunning: None declared, Rob van't Hof Shareholder of: OsteoRx Ltd, John Lockhart: None declared, Carl Goodyear Grant/research support from: AstraZeneca, BMS, Celgene, Janssen, MedAnnex, Pfizer and UCB, Speakers bureau: Abbvie